PROTOKOL TCP/IP SEBAGAI SARANA DALAM PROSES TRANSFER DATA - Yunus, Mahmud; As’ad, M. (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2012)
The study entitled Protocol TCP / IP as a means to transfer this data, carried out in laboratory STMIK PPKIA Pradnya Paramita Malang in order to find out how the working process of the protocol TCP / IP and obtain a clear picture of how the protocol TCP / IP plays a role in communication within the users computer internet. This research is the development presented in descriptive form, which is analyzing the data transfer process is one of them by using the protocol TCP / IP. The results could determine the level of error that occurred while sending and receiving data, and can be used as a reference untu networking development. Keywords:Protocol, Protocol TCP/IP, Transfer Data